2020
DOI: 10.1093/neuonc/noaa152
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial of proton craniospinal irradiation for leptomeningeal metastases

Abstract: Background Leptomeningeal metastases (LM) are associated with limited survival and treatment options. While involved-field radiotherapy is effective for local palliation, it lacks durability. We evaluated the toxicities of proton craniospinal irradiation (CSI), a treatment encompassing the entire central nervous system (CNS) compartment, for patients with LM from solid tumors. Methods We enrolled patients with LM to receive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…We evaluated a prospectively collected consecutive case series of 58 patients who were treated with pCSI between January 2018 and December 2020; 21 of the patients were enrolled in a phase I trial evaluating the safety of pCSI (NCT03520504). 19 Patients were diagnosed with LM using radiographic criteria on MRI and/or positive CSF cytology (45 patients). 6 For each patient, we collected the patient demographics, treatment history, radiation dose and fractionation, and pre- and post-pCSI MRI studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated a prospectively collected consecutive case series of 58 patients who were treated with pCSI between January 2018 and December 2020; 21 of the patients were enrolled in a phase I trial evaluating the safety of pCSI (NCT03520504). 19 Patients were diagnosed with LM using radiographic criteria on MRI and/or positive CSF cytology (45 patients). 6 For each patient, we collected the patient demographics, treatment history, radiation dose and fractionation, and pre- and post-pCSI MRI studies.…”
Section: Methodsmentioning
confidence: 99%
“… 18 We have therefore evaluated and demonstrated that proton craniospinal irradiation (pCSI) can achieve therapeutic radiation doses with relatively few side effects. 19 Currently, there are no established biomarkers of response of LM-directed therapies. We aimed to understand whether neuroimaging, CTCs in the blood, or CTCs in the CSF correlate with clinical outcomes in patients with LM treated with pCSI.…”
mentioning
confidence: 99%
“…Though prospective data and direct comparisons of proton versus photon radiation are lacking, use of proton RT may lead to lower radiation exposure decrease toxicities such as myelosuppression. 46 …”
Section: Therapeutic Advances In Leptomeningeal Diseasementioning
confidence: 99%
“…While irradiation of the entire craniospinal axis is not typically recommended due to concern for significant myelosuppression and neurotoxicity, newer techniques using protons can potentially improve the tolerability of craniospinal irradiation. 22 Intrathecal methotrexate and cytarabine have also been studied in leptomeningeal disease from solid tumors but are only modestly effective and are limited by side-effects including chemical meningitis. 23 Additionally, systemic therapies with intracranial activity, such as pemetrexed, bevacizumab, and targeted therapies, now offer better-tolerated, potentially more effective alternatives beyond intrathecal chemotherapy and WBRT, as discussed below.…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%